O olhar da fisioterapia no meio rural - estudo de caso com orizicultores de Arroio Grande, Santa Maria-RS - Dimperio, Maida Geni Siqueira (2010)
The production system of rice in Brazil, especially in southern half of the state, it holds great economic and social value. The achievements in terms of technical and discipline problems have brought the health of rural workers. The aim of this study came from the look of physiotherapy in order to emphasize the issue in the body of the farmer as an essential piece of the ratio of rice to the production of diseases. The sample consisted of 37 farmers attended the physiotherapy clinic in the period 2003 to 2008, 22 male and 15 female patients aged between 28 years and 73 years. Qualitative methods were used and based on Minayo approach, beyond the device: economy + employment relations+ body = pathologies, proposed by Foucault. The results showed that the physical therapy sessions help rice farmers to return to work in the field. The low back in males and lesion of the knee in females are the main pathologies of higher incidence. The age group most frequently comprised the age of 55 to 65. Furthermore, there was increased demand for the service of therapy in January, July and August. It was concluded that economic and technologic reasons at the work in rice production contributing to the generation of different pathologies. The rice farmers were asked during the sessions of physiotherapy on the prevention methods derived from their occupation in farming, emphasizing the Postural Education. It is recommended the need for progress in promotional activities and health care worker, looking for a specific intervention in the relationship between health and rural work, through to health surveillance and health education.